Comparative study between MSC Marc/Mentat student version and Simufact Welding for three-passed butt joint. Issue 1 (July 2020) - Napitupulu, Richard A.M.; Hutabarat, Chilinton; Manurung, Charles S.P; Manurung, Yupiter HP; Graf, Marcel
Abstract: In this research, FEM simulation was created butt joint with weld filler 3D-solid geometry. The assigned substrate element type is created and modeled on a 9 mm thickness. The three-passes of butt joint was undergoing with using the MSC Marc / Mentat student version simulation and simufact welding simulation. The butt joint designed with three passes which are penetration, filler pass and the capping for both simulations. Thermo-mechanical FEM simulations using MSC Marc / Mentat student version and simufact welding are implemented throughout the analysis. The preferred heat source model is an ellipsoid Goldak normally used for arc welding processes and weld path process in one direction. The temperature distribution caused by the welding process on the specimens must be analyzed with the same clamping conditions and the same load. Both simulations were collecting the temperature distribution to observe the calibration of software. From the results of the temperature distribution, which simulation can be assessed which is more accurate. But to be more accurate in comparing it, the two simulations must be compared directly with the experimental, with the similar material, dimensions, and welding parameters.